Epigenome editing of the potential enhancers of the schizophrenia risk genes: approaches for optimization of the genetic constructs - D. A. Abashkin; A. O. Kurishev; S. V. Smirnova; D. S. Karpov; V. E. Golimbet (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Hereditary factors contribute significantly to the development of schizophrenia. However, despite many years of research, the genetic architecture and mechanisms of the participation of genetic factors in the development of schizophrenia are not well understood. Genome-wide analyzes of genetic associations in various non-coding regions of the genome, including gene enhancers, revealed many loci associated with an increased risk of schizophrenia. In the course of the analysis of the spatial structure of the genome, we revealed the interaction of these enhancers with the promoter regions of genes involved in the metabolism of neurons. To study in more detail the functions of these genes and the participation of enhancers in their regulation, we obtained plasmid and lentiviral constructs of a functionally active transcription repressor based on the CRISPR / SpyCas9 system, as well as the endonuclease system. The use of these constructs in studies of the functions of enhancers and genes associated with the metabolism and regulation of gene expression in neurons is discussed.